2013
DOI: 10.1001/jamasurg.2013.2509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Patient, Physician, and Hospital Factors on 30-Day Readmission Following Pancreatoduodenectomy in the United States

Abstract: IMPORTANCE It is not known whether hospital and surgeon volumes have an association with readmission among patients undergoing pancreatoduodenectomy. OBJECTIVE To evaluate patient-, surgeon-, and hospital-level factors associated with readmission. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study using the Surveillance, Epidemiology, and End Results (SEER)–Medicare data with cases diagnosed from January 1, 1998, to December 31, 2005, and followed up until December 2007. Population-based cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 28 publications
6
96
1
5
Order By: Relevance
“…The influence of comorbid conditions on outcomes following surgery is well known. 33,34 Furthermore, few data were available on (neo) adjuvant treatment, for instance with FOLFIRINOX, in the included studies. All studies described only the total number of patients receiving adjuvant or neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of comorbid conditions on outcomes following surgery is well known. 33,34 Furthermore, few data were available on (neo) adjuvant treatment, for instance with FOLFIRINOX, in the included studies. All studies described only the total number of patients receiving adjuvant or neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 Prior studies have found that between 20% and 28% of patients who underwent surgical cancer treatment were readmitted to a different hospital. 7,8 One study found that approximately 15% of patients with colon cancer who underwent colectomy were readmitted within 30 days. Of those, 17% were readmitted to a different hospital from the index hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Outcome and complication rates appear to be at least partly attributable to treatment within or outside of high volume centers, while the largest share of variation appears to be due to patient-inherent factors [7,8,9]. There is currently no evidence to suggest a clinical benefit for neoadjuvant therapy in cases considered to be upfront surgically resectable [10,11].…”
Section: Resectable Disease Stagesmentioning
confidence: 99%